Identification of Gene Targets for the Sprouting Inhibitor CIPC - Thomas M. Grand; James K. Pitman; Alexander L. Williams; Lisa M. Smith; Andrew J. Fleming (Plant Direct)
ABSTRACT Sprout suppressants are widely used in industry to ensure year‐round availability of potato tubers, significantly decreasing wastage by repressing premature growth of buds on the tuber surface during storage. Despite its ban from 2020 in the EU, isopropyl N‐(3‐chlorophenyl) carbamate (also known as chlorpropham or CIPC) remains the most widely used suppressant worldwide. However, the mechanism of action of CIPC remains obscure. Here, we report on a combined targeted transcriptomic and genetic approach to identify components in the tuber bud cell‐division machinery that might be involved in CIPC's mode of action. This involved RNAseq analysis of dissected, staged tuber buds during in vitro sprouting with and without CIPC to identify lead genes, followed by the development and application of an Arabidopsis root assay to assess cell division response to CIPC in selected mutants. The ease of use of this model plant, coupled with its immense genetic resources, allowed us to test the functionality of lead genes encoding cell‐division–associated proteins in the modulation of plant growth response to CIPC. This approach led to the identification of a component of the augmin complex (a core player in mitosis) as a potential target for CIPC.